An investigation into parental involvement in the development of children's reading skills in a nursery school in northern Nigeria - Okafor, Ijeoma (2016)
This research was to investigate parental involvement in the development of children’s reading skills in a nursery school in northern Nigeria. The teachers of this school perceived that parents needed to give more support to children when it comes to reading. This study therefore sought to explore parental attitudes towards assisting children to read by attempting to provide answers to the following research questions : (1) to what extent do parents/carers’ that do and do not complete the reading log read with the children; (2) do other family members read with children; (3) what do parents/carers’ do when reading with their children;(4) does what the parents/carers’ do share any feature with any of the established reading intervention programmes; (5) is parents /carers’ completion of the reading log associated with children’s reading progress? A combination of qualitative and quantitative methods was employed. The target population comprised of twenty nine pupils along with the parent/carer who reads with the child at home and also three teachers. The instruments for data collection were questionnaires, semi structured interviews and the reading log book. Analysis of data revealed that parents always sign the reading logbook of their child and employed various approaches when reading with their child. These approaches share some features with already established reading intervention programmes. However, the quality of interaction that takes place between the child and the parent could only be deduced by the teacher through the comments in the logbook. The study concluded that there appears to be a relationship between reading progress and the signing of the logbook and in turn translates to the outcome seen in reading. There is a need not only to train parents in specific reading strategies but also to foster a more positive relationship between parents and teachers. In the light of this study, there will be need for further research to explore in depth specific challenges encountered by parents in attempting to support their child’s reading.